C-SHAPED CONFIGURATION OF THE ROOT CANAL SYSTEM - PROBLEMS AND SOLUTIONS. - Janet Kirilova; Snezhanka Topalova-Pirinska (Peytchinski Publishing, 2014)
Introduction: The patients with C-shaped configuration of the root canal system are definitely a problem in the everyday dental practice. The C-shaped configuration of the root canal can be seen in the mandibular and maxillary molars. The treatment of these teeth is very difficult. Purpose: To trace the treatment of clinical cases with C-shaped configuration of the root canal system. Material and methods: There are some different cases that are described with a C-shaped configuration of the root canal system with one, two, three and four separate root canals. Careful exploration of the floor of the pulp chamber, inspection with magnification, use of ultrasonic irrigation and a modified filling technique are of particular use. Results and Discussion: Clinical cases of a C-shaped pulp chamber and root canal system shows that this root canal aberration occurs in a wide variety and variability with a single root canal up to two, three and four separate root canals. The diameter of the root canal themselves also varies from very wide to such with a small diameter. Conclusions: Knowledge of the different anatomical variations will improve the endododntic practice of the general dental practitioners.